Statement of Reasons of Aromatherapy Use in the Cardiologic Clinics - A. T. Bykov; V. P. Terentjev; A. A. Dyuzhikov; G. V. Tchudinov; T. N. Malyarenko (Медицинский вестник Юга России, 2012)
This review demonstrates that aromatherapy seems a very perspective component of com plex rehabilitation of the patients with cardiovascular diseases. It was paid attention on the positive effects and contraindications for essential oils in these patients.